A quantitative study of eosinophil polymorphs in Hodgkin's disease. Issue 3 (March 1984) - Fuggle, W J; Crocker, J; Smith, P J
Abstract : Eosinophil polymorphonuclear leucocytes (polymorphs) were counted in 45 specimens from patients with Hodgkin's disease and five specimens from patients with reactive follicular hyperplasia. The use of chlorazol fast pink BK, a little known stain for eosinophil polymorphs, combined with image analysis facilitated rapid and reliable counting. Significant differences were found between the mean percentages of eosinophil polymorphs in the Rye subtypes of Hodgkin's disease. The numbers of eosinophil polymorphs in specimens from patients with reactive follicular hyperplasia were very low and could not be counted.